PHYLOGENETIC RELATIONSHIPS OF THE MALAY PENINSULA OTTERS (LUTRA SUMATRANA, LUTROGALE PERSPICILLATA, AND AONYX CINEREUS) BASED ON DNA SEQUENCES OF MITOCHONDRIAL D-LOOP REGION - M. K. A Rosli; P. Abdul-Patah; S. M. F. Syed-Shabthar; M. N. Burhanuddin; T. Sekiguchiα; H. Sasakiβ; M. N. Shukor; S. Yaakop; B. M. Md-Zain¥. (Journal of Animal and Plant Sciences, 2015)
Aonyx cinereus, Lutrogale perspicillata and Lutra sumatrana are three species of the Old World Otter that can be found in Peninsular Malaysia. The main objective of this research was to determine the phylogenetic relationships among these three otter genera using 401 bp DNA sequences of the D-loop region. Tree topologies were reconstructed using the Neighbor-Joining (NJ) and the Maximum Parsimony (MP) methods. Both NJ and MP trees showed that the three Otter species (A. cinereus, L. perspicillata, and L. sumatrana) formed their own monophyletic clade. The results also showed that L. perspicillata and A. cinereus were sister clades and closely related, which is supported by the bootstrap values of 85% (NJ) and 84% (MP). The two species also had a close genetic distance value of 0.031. The clades, consisting of both A.cinereus and L. perspicillata, were formed in a distinct group from L. sumatrana, which was found to be grouped with L. perspicillata in previous morphological studies. The independent monophyletic clade of L. sumatrana was supported by high bootstrap values. These results imply that L. perspicillata does not belong to the same group as L. sumatrana which has been concluded in several previous molecular studies.
Keywords: Otter; Aonyx cinereus; Lutrogale perspicillata; Lutra sumatrana; Malaysian otter; mtD-loop region